Genetic types of weathering-induced fractures in carbonate reservoirs in Fuxian area of Ordos Basin and their impact on hydrocarbon enrichment - MAO Jinxin; HE Jianhua; XIE Xinhui; DENG Hucheng; WANG Xia; CAO Feng; XING Zimeng (Youqi dizhi yu caishoulu)
The Lower Paleozoic carbonate rocks in the Ordos Basin are characterized by substantial depositional thickness and extensive distribution， with reservoirs exhibiting tight lithology， low porosity， and low permeability. The accumulation and migration of natural gas in these carbonate reservoirs are significantly influenced by storage and flow space composed of fractures and pores. Based on analytical results from core samples， thin-section observations， and production data， this study investigated the genetic types of weathering-induced fractures in Majiagou Formation of Fuxian area and their impact on hydrocarbon accumulation. The results demonstrate that weathering-induced fractures in the carbonate reservoirs are controlled by lithology， paleokarst geomorphology， and fault scale， and they can be classified into three types： karst-collapse fractures， weathering-leached fractures， and scarp-related tensile fractures. Karst-collapse fractures predominantly develop in soluble gypsum-bearing dolomites and evaporites within residual hills； weathering-leached fractures occur in dolomitic limestones on slopes and terraces； scarp-related tensile fractures form in dolomite-poor argillaceous limestones at steep unconformity surfaces. Among these fracture types， karst-collapse fractures create effective fracture networks that enhance reservoir porosity and permeability. Scarp-related tensile fractures exhibit moderate effectiveness， primarily improving permeability but failing to form complex fracture networks. Weathering-leached fractures， often mechanically filled， contribute minimally to reservoir porosity and permeability. According to production dynamics， the carbonate reservoirs in the study area are categorized into four types： karst-collapse fracture-dominated， scarp-related tensile fracture-dominated， weathering-leached fracture-dominated， and matrix-ineffective reservoirs.